Peningkatan motivasi kerja dan kinerja pegawai melalui peran lingkungan kerja, komunikasi dan disiplin kerja pegawai pada Kantor Kementerian Agama Kabupaten Sukoharjo - Lasimin Lasimin; I Gusti Putu Diva Awatara (STIE AUB Surakarta, 2025)
The aim of the research is to analyze empirically and the significance of the influence of the work environment, communication and work discipline on work motivation in improving employee performance at the Sukoharjo Regency Ministry of Religion Office. The data collection technique uses a questionnaire. The census technique sample was 50 respondents. Data analysis using instrument testing, linearity testing, hypothesis testing, and path analysis. The t test results prove that the work environment and work discipline have a significant effect on work motivation but communication has an insignificant effect; work environment, work discipline and work motivation have a significant effect on performance but communication has an insignificant effect. The results of the F test are that the work environment, communication, work discipline and work motivation have a significant effect on performance. The total R2 result is 0.959, meaning that performance is explained by the work environment, communication, work discipline and work motivation by 95.9% and the remaining 4.1% is explained by other factors outside the model. The results of the path analysis show that the direct work environment path is the most dominant and most effective path for improving employee performance. The use of work motivation as an intervening variable is not effective in this research